Bekerja dari Rumah: Analisa Kuantitatif Kinerja Para Pekerja Saat Pandemi COVID-19 - Nadila, Syarfina Mahya; Baskoro, Andhika Ajie (Jurnal Vokasi Indonesia, 2021)
The Covid-19 pandemic has forced workers to work from home. WFH intended to reduce the rate of the spread of Covid-19. This study aims to quantitatively describe the level of performance of workers while working from home (WFH) either fully or partially during the Covid-19 pandemic and the factors that influence it. This study uses a quantitative approach with an online survey. Data were analyzed descriptively and by chi-square association test. The results of this study indicate that the level of performance of workers who work from home fully or partially during the Covid-19 pandemic was low, with a percentage of 51.40% and 48.60% of respondents having a high level of performance. The results of the chi-square association test show that there is no association between gender, marital status, number of dependents in the family, number of children, age, education, employment sector, employee status, and income with the level of worker performance during work from home. The purpose of this research is an initial reference for further research with a similar theme but with different concepts, methods, and research loci.